Software certification experience in the canadian nuclear industry: lessons for the future - Wassyng, Alan; Lawford, Mark S.; Maibaum, Thomas S.E. (Proceedings of the ninth ACM International Conference on Embedded Software, 2011)
The computer controlled shutdown systems for the Nuclear Power Generating Station at Darlington, Canada, have been subject to licensing scrutinization on a number of occasions. After the first licence was approved in 1990, the licensee, Ontario Hydro, was given a number of years by the regulator to redesign the shutdown systems so that they would be more maintainable. This paper briefly describes the original certification process, lessons learned, and the subsequent development and certification of the shutdown systems. The development, internal certification processes and the regulator's certification process are briefly described. Although twenty years has elapsed since this work started, and there are new analysis techniques and tools that could be applied today, the original process itself has withstood the test of time extraordinarily well. This paper describes principles that explain why it was so successful, and how we can develop more modern approaches from this experience.